2023
DOI: 10.3390/ijms24032073
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Endothelial Lipase, High-Density Lipoprotein, and Endothelial Function Differ in Healthy Volunteers and Metabolic Syndrome Patients

Abstract: Metabolic syndrome (MS) is characterized by endothelial- and high-density lipoprotein (HDL) dysfunction and increased endothelial lipase (EL) serum levels. We examined the associations between EL serum levels, HDL (serum levels, lipid content, and function), and endothelial function in healthy volunteers (HV) and MS patients. Flow-mediated dilation (FMD), nitroglycerin-mediated dilation (NMD), serum levels of HDL subclasses (measured by nuclear magnetic resonance (NMR) spectroscopy), and EL serum levels differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…The demographic and clinical characteristics as well as the standard laboratory data of the study groups have been described previously [ 25 , 26 ] and are presented in Tables S1 and S2 . The serum levels of AOPPs were significantly higher in the patients with MS compared to the HVs (HV: 34.6 (28.9, 42.6) μmol/L vs. MS: 41.6 (30.9, 57.3) μmol/L, p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic and clinical characteristics as well as the standard laboratory data of the study groups have been described previously [ 25 , 26 ] and are presented in Tables S1 and S2 . The serum levels of AOPPs were significantly higher in the patients with MS compared to the HVs (HV: 34.6 (28.9, 42.6) μmol/L vs. MS: 41.6 (30.9, 57.3) μmol/L, p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…The study design, laboratory procedures, as well as inclusion and exclusion criteria have been described in our previous reports [ 25 , 26 ]. This study was approved by the local ethics committees of the Sisters of Charity University Hospital Centre, Zagreb, Croatia (EP 13125/17-4); the University of Zagreb, School of Medicine, Croatia; and the Medical University of Graz, Austria (31-532 ex 18/19).…”
Section: Methodsmentioning
confidence: 99%
“…The participants’ demographic and clinical characteristics have been described previously [ 24 ] and are presented in Table 1 . The HV and MS groups did not differ significantly regarding age and sex, body height, smoking status, or presence of a regular menstrual cycle in women.…”
Section: Resultsmentioning
confidence: 99%
“…The participants’ routine laboratory data have been described previously [ 24 ] and are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…EL is an enzyme produced by the endothelium, with seemingly protective effects, such as the regulation of HDL cholesterol levels, and the improvement of the qualitative properties of HDL. Klobucar et al evaluated the association between HDL properties, endothelial function, and serum EL levels in controls and MS patients [ 7 ]. The study found that the presence of MS modulates the association between HDL and endothelial function, as well as between EL and HDL.…”
mentioning
confidence: 99%